Submission by the International Livestock Research Institute (ILRI) on the elements of the four-year Sharm El-Sheikh joint work on implementation of Climate Action on Agriculture And Food Security - International Livestock Research Institute (International Livestock Research Institute, 2023)
This submission is made in accordance with paragraph 17 of decision 3/CP.27 on elements of the joint work referred to in paragraphs 14–15 of the above decision for consideration by the Subsidiary Bodies at their fifty-eighth sessions (June 2023).